Terahertz high-Q magnetic dipole resonance induced by coherent Fano interactions - Yan, Fei (2023)
High Q-factor resonance holds great promise for bio-chemical sensing and enhanced light-matter interaction. However, terahertz (THz) magnetic resonances usually demonstrate low Q-factors, resulting in huge energy radiation loss particularly in high frequency bands. Here, we show that high Q-factor magnetic dipole resonance at THz frequencies can be achieved by exploiting the coherent Fano interactions with strong field enhancements in an array composed of single metallic split-ring resonators, working at Wood-Rayleigh anomalies. It can give rise to ultrahigh Q-factor beyond 104 in the THz regime. Experimentally, the measured Q-factor of dominant magnetic dipole resonance can achieve no less than a level of ∼261 by Lorentzian fitting to the experimental data. In addition, a high Q-factor of the fundamental-order magnetic dipole resonance is demonstrated beyond 30. High-Q magnetic dipole resonance is closely associated with ultralow-damping and negative permeability in the THz band. The measurements of magnetic dipole resonances are in good agreement with the theoretical analyses. Our scheme suggests a feasible route to suppress radiative loss for enhanced THz field-matter interaction.